Existing Design Analysis of Slope Reinforcement on Clayey Soil and Its modified Alternatives (Case Study : Awunio – Lapuko National Road, Southeast Sulawesi) - R, Zahrial Firman; Khoiri, Mohamad; Siagian, Freddy (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The slopes of the Awunio - Lapuko national road section are prone to landslides, which pose a threat to the road asset management. Hard soil layer with an NSPT value >60 is found at a depth of 4 metres. The slope has been reinforced with cantilever walls (CW) and caisson as well as retaining walls and bored pile. In this research, the problem that needs to be studied is the stability of the existing slope with and without reinforcement using the cracked soils approach to obtain the factor of safety (FS) for critical conditions with the Limit Equilibrium Method (LEM). The CW is calculated for overturning stability, shear stability, foundation bearing capacity and overall stability. In addition, bored pile should also be evaluated when considered as a lateral pile based on NAVFAC, bearing capacity within the group, max & min stress and deflection capacity. The result of LEM program analysis shows the slope failure mechanism due to the existence of slip plane between weak soil layer and strong soil layer. Furthermore, the stability of existing reinforcement such as CW only or CW combined with caisson is insufficient. While the stability of reinforcement CW combined with bored pile or alternative modification such as subdrain combined with geotextile meets the requirements.